KESULITAN ANAK DALAM BELAJAR PAI SECARA DARING PADA MASA PANDEMI COVID-19 DI JORONG LAREH NAN PANJANG NAGARI ATAR KECAMATAN PADANG GANTING - Desi Nofrita; Alimir (KOLONI, 2022)
This research departs from the phenomenon experienced by fourth graders in Jorong Lareh Nan Panjang Nagari Atar, Padang Ganting District, where there are several children who have learning difficulties. Learning difficulties are learning inaccuracies caused by the possibility of brain dysfunction, difficulties in academic tasks, low learning achievement far below intelligence certainty, other causes such as blindness, emotional disturbances, sensory barriers, learning inaccuracies, or cultural poverty. During the Covid-19 Pandemic, children study at home online (on a network), this is in accordance with government regulations through the Ministry of Education and Culture and the Indonesian Ministry of Religion, implementing a policy of studying and working at home starting in mid-March 2020. Problems found, such as lack of quota to learn online, do not understand the explanation through online learning, children's learning motivation is low, it is difficult to find a network for online learning, the lack of attention given by parents. This research belongs to descriptive qualitative research, namely research methods that aim to describe in full and in depth about social reality and various phenomena that occur in the community that are the subject of research so that character traits, traits, and models are depicted with these phenomena. Data were collected using interviews and documentation. In carrying out purpose sampling interviews, namely sampling techniques with certain considerations. Based on the results of the study, it was shown that children had difficulty learning PAI online during the Covid-19 Pandemic, as seen from the author's direct interview in Jorong Lareh Nan Panjang. That During the Pandemic, children had learning difficulties, were not enthusiastic in learning, were not comfortable studying at home, lacked quota, sore eyes because they looked at their cellphones for too long, lack of parental attention, difficult networks, insufficient study materials, noisy home conditions. So it can be concluded that children really have difficulty learning in PAI subjects online during the Covid-19 Pandemic in Jorong Lareh Nan Panjang Nagari Atar, Padang Ganting District. Keyword: PAI Learning, Learning Difficulties